Keselamatan dan Kesehatan Kerja (K3) dalam Meningkatkan Keamanan dan Kepuasan Pengunjung di Taman Impian Jaya Ancol - Emenina Tarigan; Vienna Artina Sembiring; Mochamad Achmadi; Edy Marzuki; Andi Muhammad Yasin (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
This study aims to analyze the effect of Occupational Health and Safety (OHS) implementation on visitor safety and visitor satisfaction at Ancol Dreamland. The implementation of OHS in tourism destinations is an important aspect of creating a safe and comfortable environment while enhancing the quality of visitors' experiences. This study employed a quantitative approach using an explanatory survey method. Data were collected through questionnaires distributed to 150 visitors of Ancol Dreamland selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that OHS implementation has a positive and significant effect on visitor safety. OHS implementation also has a positive and significant effect on visitor satisfaction. Furthermore, visitor safety has a positive and significant effect on visitor satisfaction. The mediation test results reveal that visitor safety significantly mediates the relationship between OHS implementation and visitor satisfaction. The findings demonstrate that OHS implementation is a strategic factor that can improve visitor safety and satisfaction both directly and indirectly. Therefore, tourism destination managers should strengthen OHS implementation to continuously enhance service quality and visitor experiences. Keywords: occupational health and safety (OHS), visitor safety, visitor satisfaction